Strategi Preventif Pemerintah Nusa Tenggara Barat dalam Mewujudkan Zero Unprocedural PMI - Septi Hariani; Najamuddin Khairur Rijal (Department of International Relations, Hasanuddin University, 2023)
Indonesian migrant workers are the second largest contributor to the country and play a role in several economic sectors. Unfortunately, this is followed by the emergence of cases that harm migrant workers, which are often caused by lack of knowledge, sources of information and the emergence of brokers who end up in cases of sending illegal migrant workers or often called PMI Unprocedural. The emergence of various modes under the pretext of traveling, visiting and worshiping Umrah in order to escape the surveillance and screening of immigration officers. It is known that West Nusa Tenggara Province is the 3rd largest province that sends PMI abroad. This study uses a descriptive type of research. Based on the results of the study, it is known that preventive efforts have been continuously issued by the West Nusa Tenggara regional government to protect the rights and safety of migrant workers from various threats such as human trafficking syndicates, accidents while traveling, violence at work, and protecting workers from non-payment of salaries by employers. , etc. In addition, it is known that the NTB Provincial Government continues to develop in the formation of Desmigratif and Zero Cos to be able to guarantee the rights of CPMI, PMI, and their families. Pekerja migran indonesia menjadi penyumbang terbesar kedua negara dan memaninkan peran pada beberapa sektor ekonomi. Namun sayangnya hal ini diikuti oleh munculnya kasus-kasus yang merugikan para pekerja migran, yang sering kali disesbabkan oleh kurangnya pengetahuan, sumber informasi serta munculnya para calo yang berakhir pada kasus pengiriman pekerja migran ilegal atau sering disebut PMI Unprocedural. Munculnya berbagai modus dengan dalih berwisata, berkunjung, dan beribadah umroh untuk dapat lolos dari pengawasan dan penjaringan petugas keimigrasian. Diketahui bahwasanya Provinsi Nusa Tenggara Barat menjadi Provinsi terbesar ke-3 yang mengirimkan PMI ke luar Negeri. Penelitian ini menggunakan jenis penelitian deskriptif. Berdasarkan hasil penelitian, diketahui bahwa Upaya-upaya preventif terus menerus dikeluarkan pemerintah daerah Nusa Tenggara Barat untuk melindungi hak dan keselamatan pekerja migran dari berbagai ancaman seperti sindikat penjualan manusia, kecelakaan saat diperjalanan, kekerasaan saat bekerja, dan melindungi pekerja dari tidak dibayarkannya gaji oleh majikan, dll. Selain diketahui bahwa Pemerintah Provindi NTB terus melakukan pengembangan dalam pembentukan Desmigratif dan Zero Cos untuk dapat menjamin hak para CPMI, PMI, dan keluarganya.